Cholesterol-rich lipid rafts play a critical role in bovine parainfluenza virus type 3 (BPIV3) infection. (October 2017) - Li, Liyang; Yu, Liyun; Hou, Xilin
Abstract: Lipid rafts are specialized lipid domains enriched in cholesterol and sphingolipid, which can be utilized in the lifecycle of numerous enveloped viruses. Bovine parainfluenza virustype3 (BPIV3) entry to cell is mediated by receptor binding and membrane fusion, but how lipid rafts in host cell membrane and BPIV3 envelope affect virus infection remains unclear. In this study, we investigated the role of lipid rafts in the different stages of BPIV3 infection. The MDBK cells were treated by methyl-β-cyclodextrin (MβCD) to disrupt cellular lipid raft, and the virus infection was determined. The results showed that MβCD significantly inhibited BPIV3 infection in a dose-dependent manner, but didn't block the binding of virus to the cell membrane. Whereas, the MDBK cells treated by MβCD after virus-entry had no effects on the virus infection, to suggest that BPIV3 infection was associated with lipid rafts in cell membrane during viral entry stage. To further confirm lipid rafts in viral envelope also affected BPIV3 infection, we treated BPIV3 with MβCD to determine the virus titer. We found that disruption of the viral lipid raft caused a significant reduction of viral yield. Cholesterol reconstitution experiment showed that BPIV3 infection was successfully restored by cholesterol supplementation both in cellular membrane and viral envelope, which demonstrated that cholesterol-rich lipid rafts played a critical role in BPIV3 infection. These findings provide insights on our understanding of the mechanism of BPIV3 infection and imply that lipid raft might be a good potential therapeutic target to prevent virus infection. Highlights: The infectivity of BPIV3 was inhibited by MβCD in a dose-dependent manner. Cholesterol depletion had not effect virus binding to cells. Removal of viral envelope cholesterol can inhibit the infection of BPIV3.